Youth politics in East Germany the Free German Youth Movement, 1946-1968 - McDougall, Alan (Alan James) (Oxford historical monographs., 2004)
In East Germany during the 1950s and 1960s young people were a constant problem for the communist authorities - and in particular for the communist youth organization, the Free German Youth (FDJ). This work provides an in-depth study of the often troubled relationship between the FDJ and East German youth during this period.